2003
DOI: 10.1029/2001jd000443
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and decadal patterns of soil carbon uptake and emission along an age sequence of burned black spruce stands in interior Alaska

Abstract: [1] Postfire changes in the local energy balance and soil chemistry may significantly alter rates of carbon turnover in organic-rich soils of boreal forests. This study combines field measurements of soil carbon uptake and emission along a 140-year chronosequence of burned black spruce stands to evaluate the timescales over which these disturbance effects operate. Soil CO 2 efflux increased as a function of stand age at a mean rate of 0.12 Mg C ha À1 yr À2 up to a maximum of 2.2 Mg C ha À1 yr À1 in the 140-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 47 publications
(72 reference statements)
6
76
0
Order By: Relevance
“…Instead, we assessed the functional diversity of bacteria, which represent another decomposer group that can metabolize a wide range of substrates. O'Neill et al (2003) have found that soil respiration declines in the first several years following fire near our sites; delays in recovery of microbes that perform mineralization may be a possible mechanism underlying this response.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Instead, we assessed the functional diversity of bacteria, which represent another decomposer group that can metabolize a wide range of substrates. O'Neill et al (2003) have found that soil respiration declines in the first several years following fire near our sites; delays in recovery of microbes that perform mineralization may be a possible mechanism underlying this response.…”
Section: Introductionmentioning
confidence: 63%
“…All sites are located within a 100-km 2 landscape on gently sloped alluvial flats. Portions or all of this chronosequence have been used to assess effects of fire on soil carbon fluxes (O'Neill 2000, O'Neill et al 2003, soil chemistry (King et al 2002), and hydrogen fluxes (Rahn et al 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The area is mostly covered by forest and shrub landscapes [24] and underlain by dis-continuous permafrost. The Alaskan interior between the Alaska and Brooks Mountain Ranges has a strong continental climate with moderate temperatures and precipitation in summer and exceedingly cold and dry weather in winter [25]. The average minimum and maximum annual temperatures in Big Delta station , which is located in the study area, are −6.9 °C and −2.7 °C, respectively.…”
Section: Study Area and Datamentioning
confidence: 99%
“…Generally, the soil water balance is modeled in two approaches in terrestrial ecosystem models. Models, such as CENTURY (Parton et al, 1987), the Carnegie-AmesStanford (CASA) (Potter et al, 1996), and BIOME-BGC (Kimball et al, 1997), consider the soil mainly as a storage reservoir, or "bucket". The bucket fills with water when precipitation is greater than evaporation, and no movement of soil water between adjacent soil layers occurs.…”
Section: Introductionmentioning
confidence: 99%